Making Toronto modern architecture and design ; 1895 - 1975 - Armstrong, Christopher 1942- (McGill-Queen's/Beaverbook Canadian foundation studies in art history, 2014)
"In the final years of the nineteenth century, Toronto architects started to consider how their city, through progressive architecture and urban planning, could be made "modern." Making Toronto Modern constructs Toronto's architectural past to create a compelling narrative of how new ideas about modernism were debated, received, and embodied in new buildings"--Back cover